KNOWLEDGE SHARING IN THE SUPPLY CHAIN NETWORK: FINDINGS FROM SELECTED âWARUNG TEGALâ BUSINESS IN BANDUNG - Sunardi, Oki (Teknik dan Ilmu Komputer, 2012)
Knowledge sharing activity has been considered as the key activity in knowledge management. This study aims at exploring and conceptualizing knowledge sharing process and behaviors of the members of Warung Tegal (Warteg) business supply chain network. The study specifically examines the role of Warteg in the knowledge sharing process. Using informal interviews to five selected Warteg owners, value chain, supply chain network, and knowledge sharing process are explored. Knowledge sharing behavior among the actors in the network is then analyzed. The study found that most of the Warteg owners chose similar source of suppliers which shared similar certain knowledge to the Warteg owners. Suppliers play a significant role in ownersâ decision making. The difference lies on the decisions taken by owners after knowledge have been transferred.Â Keywords: knowledge sharing, supply chain, warteg, decision making